ENHANCING HEALTHCARE QUALITY AMONG COMMUNITY HEALTH FACILITIES WITH RESULTS-BASED FUNDING IN EASTERN UGANDA - Festo Nyende Tusubira; Geoffrey Nuwagaba (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2024)
This study examines the effects of Result-Based Funding (RBF) on the healthcare quality in Health Centre (HC) III in Jinja District concerning patient waiting time, drug stockout, choice of healthcare, and availability of essential medicines in Uganda’s community health facilities. The research used a cross-sectional survey design and found that results-based funding like timely funding, and funding size had a significant relationship with healthcare quality. Management practices also had a strong positive correlation with healthcare quality, but most importantly management practices moderated the relationship between results-based funding and healthcare quality among Health Centre IIIs in Jinja District. The study recommends increasing the size of RBF, sending or providing timely funds, improving the fund size, and building and maintaining results-based incentives for staff that implement activities at the health facilities. Health Centre management to continue activity planning, improve staffing levels, carry out regular monitoring of all activities supported by the RBF programme, and ensure that storage capacity is enabled for the safety of essential medicines and other stores.